(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper examines the historical development and contemporary status of the Uzbek language, emphasizing its legal, social, and cultural significance in the modern Republic of Uzbekistan. It also explores the evolution of national literature, its major stages, and the contributions of prominent representatives who played a crucial role in shaping Uzbek literary thought. The study highlights the strong interconnection between language and literature, showing how literary figures have enriched the Uzbek language and contributed to national identity. Finally, the work summarizes the importance of preserving and further developing the Uzbek language and literature in the context of globalization.